As representações mentais na execução musical : o caso dos estudantes de flauta doce de uma escola pública de Pacatuba-CE - Sousa, Natanael Martins de (2020)
This research investigated how mental representations can contribute to the musical education of students in a recorder class at a public school in the city of Pacatuba-CE. Mental representations are images that arise from an individual’s memory due to a stimulus and that are constructed through their experiences and knowledge. The objective of this research was to identify how mental representations can help the musical education of students in a recorder class at a public school in the city of Pacatuba-CE, in the Fortaleza metropolitan area. To that end, we carried out an experiment in two stages with the aforementioned students. The research protocol was organized based on the following question: “What were you thinking about while you played the song ‘Asa Branca’?”, in order to categorize and analyze students’ answers according to the mental images created during the execution of the song. Methodologically, this research consists of a case study, with qualitative approach. Results indicated that mental representations contributed to students’ learning from the moment they consciously used them as a supporting tool guiding their practices, their aesthetic choices and their performance.